SENSORY EXPERIENCES OF AUTISTIC PEOPLE AND SCIENCE TEACHING - Moura, Tiago Fernado Alves de [UNESP]; Camargo, Eder Pires de [UNESP] (Inst Educacao Univ Lisboa, 2022)
This article aims to present and discuss the contributions of the use of multisensory materials in the development of students with autism in science classes. For this purpose, this study presents an inquiry-based teaching approach in which a toy car moves on an inclined plane. Teaching/learning situations were used in which the concepts of force and movement were explored. As instruments for data collection, audio records were used, which were later transcribed and annotated in field notebooks. The data obtained were tabulated and categorized according to the distinct stages of a Content Analysis. The multisensory materials contributed to the teaching/learning process of the students by contemplating different perceptive styles, such as the visibility and sound effects of the toy car. The manipulation of objects provided group work and the development of social and psychomotor skills. Through the activity, the learners shared and reformulated hypotheses about the physical phenomena presented.
Keywords: autism; science; multisensory; inquiry-based teaching approach; force and movement